Is a plea really a bargain?: an analysis of plea and trial dispositions in New York City - Kutateladze, Besiki (Crime & delinquency, 2018)
The study challenges the common notion that plea bargaining is necessarily beneficial to defendants. It examines the factors influencing the likelihood of taking a misdemeanor case to trial, and the probability of acquittal upon reaching trial. Defendants charged with more serious crimes, persons crimes, crimes with victims, and represented by private attorneys were more likely to go to trial than to be pleaded out. By contrast, very few factors influenced trial outcomes, and the effect of race was fairly weak. Perhaps most important is the finding that two in five cases going to trial resulted in acquittal, showing that guilt is not a foregone conclusion which may provide leverage to defendants in the plea-bargaining process.